A new technical framework for security, trust and privacy (STP) of RFID system / Mohd Faizal Mubarak - Mubarak, Mohd Faizal (Institute of Graduate Studies, UiTM, 2015)
Future trend of RFID system is moving towards integration with other devices, and hence making it more pervasive. Even though RFID technology brings numerous benefits, it also comes with potential security and privacy threats. In this thesis, we investigate how the integration and interconnection of RFID system with other devices introduce security vulnerabilities which could be exploited by attackers and adversary systems equipped with advanced techniques and attacking tools to achieve their evil objectives. We examined past works on RFID with privacy-preserving solutions dealing with issues on system integrity and availability. We found out that these unprotected RFID system without integrity verification could also be subjected to malicious code attacks and impersonation attacks. We found a solution that could exactly protect the RFID system in three main protection areas, namely security, trust, and privacy (STP). We believe that we have used a unique approach in our research study because we have taken into account all potential issues and we tackle them in a unified and integrated way. Our main contribution is that we proposed a unified STP protection in RFID framework which protected against unauthorized access and adversary attacks. We call this framework as MF-JaSa2 RFID framework….